THE FACTORS OF THE RISE OF ITALIAN RADICAL RIGHT WITH THE REFLECTION ON ITS FASCIST ELEMENTS - Lakić, Danijela (Political Review, 2023)
The topic of the paper is the Italian radical right, which won a landslide victory in last year’s elections and formed the most right-wing government since World War Two. The aim of the paper is to determine the reasons for strengthening the Italian right’s fascist wing through the analysis of its history and the circumstances of its activity and to show whether the fears of the European Union that fascism returned to one of its founding countries are justified. The main difference between the modern radical right and fascism is its acceptance of democracy and political pluralism. It is fundamentally different from classic fascist parties, it is characterized by populism and not elitism, nativism instead of racism, it is not autocratic but democratic. Up until the nineties, the term right was equated with fascism in Italian political discourse, so a true right did not even exist as a regular actor in political life. The conclusion of the paper is that Italy never truly broke with fascism, the process of defascification was not carried out in its entirety. The victory of the radical right, in which the youngest party, Fratelli d'Italia, which is the offspring of Mussolini’s party, dominates is the result of the EU membership itself and the waves of crises it faces, the specificities of the Italian political system, the peculiarities of Italian fascism, a general weakening of liberal order with the transformation of the left and the right. The right did not win a two-thirds majority in the Parliament which is a prerequisite for the government of the right to alter the constitution without a referendum, and so the legal realization of radical policies is under control. There is minimal risk of the deterioration of relations with the European Union because, regardless of the current more moderate approach, Giorgia Meloni advocated the abandoning of the Eurozone and conceptually different structure of The Brussels regime.
Keywords: Italy; radical right; facism; European Union